The Effectiveness of Internal Control in Amal Usaha Pendidikan Muhammadiyah as a Fraud Prevention - Hanif, Aisha; Widodo, Heri; Dina Dwi Oktaviarini (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the effectiveness of the internal control system in preventing fraud in Muhammadiyah Education Charities. The background of this study departs from the importance of accountable and transparent governance in the management of Muhammadiyah educational institutions, which have a strategic role in developing the people’s character and intellect. The research uses a qualitative approach with a case study method, relying on in-depth interviews, observations, and documentation as data collection techniques. Data was obtained through in-depth interviews with LPPK auditors, school principals, main treasurers, cash receipt and expenditure staff, direct observation, and documentation. Data analysis was carried out using thematic analysis, which involves data reduction, presentation, and conclusion drawing. The research will be carried out from August to November 2024. The study results show that implementing the five components of internal control according to the COSO framework is still not optimal, especially in the aspects of the control environment, risk assessment, control activities, information, and communication. It was found that the lack of written SOPs, awareness of the importance of risk assessment, and weak communication systems are the main inhibiting factors in preventing fraud. In conclusion, the internal control system in this education unit still needs structural and cultural strengthening to build more effective governance and integrity. This research contributes by mapping the weaknesses of internal control in Muhammadiyah's AUM based on the COSO framework and offering the integration of Muhammadiyah values in fraud prevention. The novelty of this research is an effort to connect the principles of modern internal control (COSO) with the values of progressive Islamic ethics of Muhammadiyah in building accountable and integrity educational governance.